ダイ15ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1974 - 鈴木, 剛彦; スズキ, タケヒコ; 安富, 裕二; ヤストミ, ユウジ; 林, 則雄; ハヤシ, ノリオ; 篠原, 健夫; シノハラ, タテオ; Suzuki, Takehiko; Yasutomi, Yuji; Hayashi, Norio; Shinohara, Tateo (国立極地研究所, 1977)
P(論文) この報告は第15次南極地域観測越冬隊気象部門が,力点をおいて行った業務とその主な成果を述べたものである.気象観測については,世界気象機構(WMO)の勧告にしたがって,3時間毎の地上気象観測を1974年2月1日から,1日2回の高層気象観測を同年3月1日から,定常的に実施した.今回導入された新しい施設は,アンモニア分解ガス発生装置と10立方メートルの水素ガスタンクとである.第15次越冬観測期間中,特記される気象の概況は次の通りである.1)5月にインド洋高気圧が南極大陸付近にまで張り出してきたため,自記気圧計では27日に,1025.0 mbを記録した.2)6月,11月,12月は好天が続き,特に11月には,日照率75%にまで達し,晴天日数も16日を数えた.気象観測に関連したものとして,1)オゾンゾンデ観測の結果から,突然昇温が起こっている高さと,オゾン密度最大の高さとが一致していることが判明した.2)新たにオーバーホールしたオゾン分光光度計(島津No.5706)を搬入して,オゾン全量観測を行った.3)三種類のショットフィルターを備えた直達日射計を使って/大気混濁度の測定を行い,昭和基地を全球的なバックグラウンド汚染基準観測点として整備する場合の予備的調査を行った. This paper states the results of the meteorological observation carried out by the 15th JARE in 1974 at Syowa Station. In accordance with the recommendation by WMO (World Meteorological Organization), surface observations were carried out every three hours from February 1 and aerological observations carried out twice a day from March 1 in 1974. The new type hydrogen generator, which resolves ammonium into hydrogen and nitrogen, was set up and the mixed gas was stored in the tank, from which balloons could be filled up anytime. Meteorological characters of the year 1974 are as follows; 1) In May the Indian Ocean High had great influence over the Antarctic Ocean, and the barograph recorded 1025.0 mb on the 27th. 2) In June, November and December the fine weather lasted for a long time. In November the percentage of possible sunshine attained to 75% and the number of clear days was 16. The results of ozone sonde (KC-68) observations showed that in the stratospheric sudden warming phenomena the temperature rise is closely related with the ozone-density increase. Observations of the total amount of ozone were carried out with the ozone spectrophotometer. The turbidity of the atmosphere was also calculated by means of the pyrheliometer and filter technique. departmental bulletin paper